2002
DOI: 10.1152/ajpheart.00997.2000
|View full text |Cite
|
Sign up to set email alerts
|

UDP acts as a growth factor for vascular smooth muscle cells by activation of P2Y6receptors

Abstract: linge. UDP acts as a growth factor for vascular smooth muscle cells by activation of P2Y 6 receptors. Am J Physiol Heart Circ Physiol 282: H784-H792, 2002; 10.1152/ajpheart.00997.2000.-Mitogenic effects of the extracellular nucleotides ATP and UTP are mediated by P2Y 1, P2Y2, and P2Y4 receptors. However, it has not been possible to examine the highly expressed UDP-sensitive P2Y6 receptor because of the lack of stable, selective agonists. In rat aorta smooth muscle cells (vascular smooth muscle cells; VSMC), UD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 37 publications
4
68
0
Order By: Relevance
“…Moreover, the dependence of NF-B translocation and osteoclast survival on UDP concentration observed in the present study is consistent with the concentration dependence reported for P2Y6 receptor-mediated responses in other systems (e.g. 34,35). In the present study, concentrations of INS48823 as low as 1 M stimulated osteoclast survival, perhaps reflecting its greater stability compared with UDP, which is hydrolyzed rapidly by ectonucleotidases (35).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the dependence of NF-B translocation and osteoclast survival on UDP concentration observed in the present study is consistent with the concentration dependence reported for P2Y6 receptor-mediated responses in other systems (e.g. 34,35). In the present study, concentrations of INS48823 as low as 1 M stimulated osteoclast survival, perhaps reflecting its greater stability compared with UDP, which is hydrolyzed rapidly by ectonucleotidases (35).…”
Section: Discussionsupporting
confidence: 92%
“…34,35). In the present study, concentrations of INS48823 as low as 1 M stimulated osteoclast survival, perhaps reflecting its greater stability compared with UDP, which is hydrolyzed rapidly by ectonucleotidases (35).…”
Section: Discussionsupporting
confidence: 44%
“…A novel role for P2Y 2 receptors in the development of atherosclerosis has been suggested, whereby UTP induces vascular cell adhesion molecule-1 expression in coronary artery endothelial cells that mediate the recruitment of monocytes (Seye et al, 2003). The long-term (trophic) roles of purinergic signaling in vascular smooth muscle and endothelial cell proliferation and death have been implicated in atherosclerosis and restenosis and suggest the exploration of therapeutic strategies in relation to these events (Erlinge et al, 1998;Burnstock, 2002b;Hou et al, 2002;Wang et al, 2003b).…”
Section: Atherosclerosis and Restenosismentioning
confidence: 99%
“…UDP has been shown to provoke the contraction of mouse mesenteric arteries, rat and human cerebral arteries, and mouse renal arteries (Vial and Evans, 2002;Malmsjö et al, 2003;Vonend et al, 2005). Furthermore, UDP is a growth factor for aortic smooth muscle cells in vitro (Hou et al, 2002). UDP induced an endothelium-dependent relaxation of the mouse aorta, which, like a similar action of UTP, was maintained in P2Y 2 Ϫ/Ϫ mice, suggesting the possible involvement of the P2Y 6 receptor (Guns et al, 2005(Guns et al, , 2006.…”
mentioning
confidence: 98%